Signing Blank Checks: The Roles of Disclosure and Reputation in the Face of Limited Information - Pawliczek, Andrea; Skinner, A. Nicole; Zechman, Sarah L. C. (The Accounting Review, 2024)
ABSTRACT We examine how disclosure and manager reputation influence capital raised when there is no commercial substance underlying the investment. Special Purpose Acquisition Companies (SPACs or “blank check” companies) do not have operations or substantive assets at the IPO but promise to use the funds raised to acquire a private firm, generally within two years. Given the lack of commercial substance and historically poor ex post performance, it is unclear what SPACs disclose at the IPO and why investors invest. Although disclosure is important in traditional IPOs, the underlying information available differs for SPACs. Nonetheless, our evidence suggests disclosures are useful to SPAC investors, although differently than for traditional IPO investors. We also examine manager reputation and find prior SPAC or CEO experience and celebrity status are associated with funds raised. Even when an investment lacks commercial substance, disclosure and reputation are important for investing decisions. Data Availability: Data are available from the public sources cited in the text. JEL Classifications: G24; G34; M41; M50.